2022
DOI: 10.1055/a-1904-6025
|View full text |Cite
|
Sign up to set email alerts
|

Can We Predict Feto-Maternal Adverse Outcomes of Vacuum Extraction?

Abstract: Introduction Vacuum extraction (VE) is an important modality in modern obstetrics, yet sometimes results in maternal or neonatal adverse outcomes, which can cause a lifetime disability. We aimed to characterize potential risk factors for adverse outcomes that in retrospect would have led the physician to avoid the procedure. Materials and Methods Retrospective cohort of 3331 singleton pregnancies, ≥ 34 w delivered by VE. 263 deliveries (7.9%) incurred a VE-related feto-maternal adverse outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…These characteristics were more frequently displayed in the GDM-IPH group; therefore, this could explain the higher rate of vaginal operative delivery. This goes along with a recent analysis, that was able to demonstrate an association of vacuum extraction and nulliparity [25]. Ramos et al examined women requiring operative delivery assistance and found a decreased likelihood of vaginal operative delivery in women with pre-pregnancy obesity [26].…”
Section: Discussionmentioning
confidence: 64%
“…These characteristics were more frequently displayed in the GDM-IPH group; therefore, this could explain the higher rate of vaginal operative delivery. This goes along with a recent analysis, that was able to demonstrate an association of vacuum extraction and nulliparity [25]. Ramos et al examined women requiring operative delivery assistance and found a decreased likelihood of vaginal operative delivery in women with pre-pregnancy obesity [26].…”
Section: Discussionmentioning
confidence: 64%
“…However, the odds of a vaginal operative delivery were significantly increased if women were underweight and/or nulliparous. This goes along with a recent analysis, that was able to demonstrate an association of vacuum extraction and nulliparity (25). Ramos et al examined women requiring operative delivery assistance and found a decreased likelihood of vaginal operative delivery in women with prepregnancy obesity (26).…”
Section: Figurementioning
confidence: 63%
“…The key distinctions between the two are the vacuum mechanism (handheld pump vs. conventional vacuum) and the traction pole (flexible in the Kiwi and rigid in the Mityvac). Recent data suggest that the use of the Kiwi OmniCup minimizes feto-maternal birth trauma, as compared to the Mityvac cup [19,20]. Failure rates using the Kiwi OmniCup vary [21][22][23], and are reported at around 1.4% in a previous publication from our institution [24].…”
Section: Introductionmentioning
confidence: 86%